I dont understand how you got this part
(Original post by TiTo20)
The way I did this question was to look at the first equation on the page.
You can see that it is MnO4- + 8H+ +5 e- --> Mn2+ + 4H2O.
In the second equation, it is 2MnO4-... Etc etc.
You have to times the first equation by two to get 2MnO4- for the second equation, so do that now.
2MnO4- + 16H+ + 10e- --> 2Mn2+ +8H2O.
If you think of it as two equations, you can take away the new equation above from the second equation, so you get :
2MnO4- + 6H+ + 5H2O2 - 2MnO4- - 16H+ - 10e- --> 2Mn2+ + 8H2O + 5O2 - 2Mn2+ - 8H2O
Cancel anything out if you can and you get left with :
5H2O2 -10H+ - 10e- --> 5O2
Move all the 'negative' signs to the other side (in those case, it's the H+ and the e-) and change them to 'positives'
5H2O2 ---> 5O2 + 10H+ + 10e-
Simplify (everything goes into 5 so divide by 5)
H2O2 --> O2 + 2H+ + 2e-
That's your answer! =]
Did you understand the process I went through?
This was posted from The Student Room's iPhone/iPad App
OH WAIT you mean cancel eaach side of the equation by itself not opposite sides?!!
Last edited by asaaal; 07-06-2012 at 14:13.